Budgeting Participation and Organizational Commitment to Budgetary Gaps with Information Asymmetry as a Moderating Variable - Junaidi Yakub; Irfan Zamzam; Johan Fahri (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This research is quantitative research with simple regression analysis and moderate regression analysis. The objectives of this study: firstly, to analyze the effect of budgetary participation in budget slack, secondly, to analyze the effect of organizational commitment on budget slack, thirdly, to analyze the effect of budgetary participation on budget slack with information asymmetry as a moderating variable, fourthly, to analyze the effect of organizational commitment on the relationship between information asymmetry and budget slack. The sample in this study was 47 respondents in the Tidore Islands city government. Based on the research results, it is known that budgetary participation has a positive effect on budget slack, organizational commitment has a negative effect on budget slack and information asymmetry does not moderate the relationship between budgetary participation and organizational commitment to budget slack.